Computer Simulation in Financial Accounting. - Stone, Donald E. (The Accounting Review, 1973)
The article presents the author's examination of incorporating instruction in computers, programming and electronic data processing concepts into the accounting curriculum. the author observed that the introductory course in computers is a significant pre-requisite to effective integration of the computer in the functional courses. He also observed that data-based systems and user-oriented software enhance the flexibility and diversity of learning experience available to students. He also added that direct incorporation of computers into the accounting curriculum can augment the student's ability to make efficient use of the computer and help him attain a greater depth of understanding of the subject matter.